- 7x + y = 4
8x - 3y = 1
X=
y =
Answer:
x=-1 y=-3
............
Answer:
(−1,−3) or x=−1,y=−3
Step-by-step explanation:
Solve for the first variable in one of the equations, then substitute the result into the other equation.
Answer:
For four days it would be $19.8. For seven days it would be $24.9
Step-by-step explanation:
4 days:
$4.70 x 4 + 1= 19.8
7 days:
$4.70 x 7 = $24.9
I took away 1 from the 4 day equation because the question said you get a dollar off if you return the dvd before 5 days.
Hope this helps!
~Starr
The distance of the run is 13.125 miles. The total time for the slower jogger was found to be 2.625 hours. Thus, both joggers ran the same distance, but at different speeds resulting in different finish times.
The problem deals with the concept of relative speed in mathematics. To find the distance of the run, we first need to figure out the time it took for each jogger to finish the run. We know that the slower jogger finished 45 minutes after the faster one. Since the speed equivalence is expressed in miles per hour (mph), let's convert 45 minutes into hours by dividing 45 by 60, giving us 0.75 hours.
Given that the slower jogger runs at 5 mph, and they took 0.75 hours longer than the faster one, we know they ran for a certain time 't', so we can represent this as t = total time of slower jogger's run.
The faster jogger ran at 7 mph. Since the jogger was 0.75 hours ahead of the slower one, the time would be represented by t - 0.75 hours = total time of faster jogger's run. The distance travelled by each jogger is 'speed x time'.
Following this, we equal these distances because it's the same course: 5t = 7(t - 0.75).
Solving this equation gives us t = 2.625 hours (total time for slower jogger). To find the run's distance, we can now substitute total time into either jogger's speed x time calculation. We'll use the slower jogger here: Distance = 5t = 5*2.625 = 13.125 miles.
#SPJ3
Answer:
Step-by-step explanation:
Given vectors:
When subtracting vectors, we subtract the elements in the same position from one vector from the elements in the same position of the other vector. Therefore, subtracting vector b from vector c gives:
When multiplying a vector by a constant, we multiply each component of the vector by that constant. Therefore, multiplying vector a by 3 gives:
Multiply (c - b) by 1/4:
Finally, subtract the vectors:
Answer:
rational
Step-by-step explanation: